Time‐multiplexing method using dual ferroelectric liquid crystal shutters for light field 3D display - Sun, Zhi‐Bo; Yuan, Zheng‐Nan; Huo, Yi‐Peng; Cheng, Yue‐Chu; Cheung, Alex Yuk Lung; Vashchenko, Valerii; Vashchenko, Olena; Srivastava, Abhishek; Kwok, Hoi‐Sing (Journal of the Society for Information Display, 2025)
Ultrafast liquid crystal light valves are extensively utilized in high‐refresh‐rate displays and light beam control and shaping applications. Ferroelectric liquid crystals, characterized by their ability to achieve microsecon response times when driven by a 5 V voltage, are particularly well‐suited for array‐type liquid crystal light valves, such as display screens or adjustable liquid crystal gratings. This study employs optimized ferroelectric liquid crystal materials that exhibit high contrast (~1,000:1), ultra‐fast response times (<20 μs), and polarity‐dependent binary switching at low operating voltages (5 V) to develop an array liquid crystal light valve suitable for time‐sequential light field 3D displays. Combined with high frame rate display screen, a naked eye 3D display without resolution loss can be achieved. The challenges associated with the independent control of ferroelectric liquid crystals during array light valve operation were analyzed and resolved, resulting in an array‐type ultrafast ferroelectric liquid crystal light valve compatible with conventional liquid crystal driving schemes. An array‐type ultrafast ferroelectric liquid crystal light valve compatible with conventional liquid crystal driving schemes was fabiricated and studied. The charge compensation issues in binary switched FLC are overcomed by combining a reference FLC cell and another array type FLC valve array.